Genotype Profile of Global EYS-Associated Inherited Retinal Dystrophy and Clinical Findings in a Large Chinese Cohort - Xu, Ke; Chen, De-Fu; Chang, Haoyu; Shen, Ren-Juan; Gao, Hua; Wang, Xiao-Fang; Feng, Zhuo-Kun; Zhang, Xiaohui; Xie, Yue; Li, Yang; Jin, Zi-Bing (Frontiers in Cell and Developmental Biology, 2021)
Purpose: The aim of this study was to probe the global profile of the EYS-associated genotype-phenotype trait in the worldwide reported IRD cases and to build a model for predicting disease progression as a reference for clinical consultation. Methods: This retrospective study of 420 well-documented IRD cases with mutations in the EYS gene included 39 patients from a genotype-phenotype study of inherited retinal dystrophy conducted at the Beijing Institute of Ophthalmology and 381 cases retrieved from global reports. All patients underwent ophthalmic evaluation. Mutations were revealed using next-generation sequencing, followed by Sanger DNA sequencing and real-time quantitative PCR analysis. Multiple regression models and statistical analysis were used to assess the genotype and phenotype characteristics and traits in this large cohort. Results: A total of 420 well-defined patients with 841 identified mutations in the EYS gene were successfully obtained. The most common pathogenic variant was a frameshift c.4957dupA (p.S1653Kfs*2) in exon 26, with an allele frequency of 12.7% (107/841), followed by c.8805C>A (p.Y2935X) in exon 43, with an allele frequency of 5.9% (50/841). Two new hot spots were identified in the Chinese cohort, c.1750G>T (p.E584X) and c.7492G>C (p.A2498P). Several EYS mutation types were identified, with CNV being relatively common. The mean age of onset was 20.54±11.33 (4–46) years. Clinical examinations revealed a typical progression of RPE atrophy from the peripheral area to the macula. Conclusions: This large global cohort of 420 IRD cases, with 262 distinct variants, identified genotype-phenotype correlations and mutation spectra with hotspots in the EYS gene. Our findings provide critical information for clinical genetic diagnosis, as well as therapeutic development, for EYS-associated retinal degeneration.